2020
DOI: 10.1038/s41598-020-77930-1
|View full text |Cite|
|
Sign up to set email alerts
|

Human volunteer study of the decontamination of chemically contaminated hair and the consequences for systemic exposure

Abstract: The decontamination of exposed persons is a priority following the release of toxic chemicals. Efficacious decontamination reduces the risk of harm to those directly affected and prevents the uncontrolled spread of contamination. Human studies examining the effectiveness of emergency decontamination procedures have primarily focused on decontaminating skin, with few examining the decontamination of hair and scalp. We report the outcome of two studies designed to evaluate the efficacy of current United Kingdom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Ethical approval was given by Public Health England's Research Ethics Group. As part of a series of human volunteer studies eleven (power = .909, based upon 4 ) participants completed a controlled crossover study in which their skin was dosed separately with MeS (1:1 mixture with vegetable oil) and BeS (each with 4mg/ml of uorescent marker Invisible Red S 4,8 ) at sites on both shoulders (Figure S1). The shoulder was chosen as it was a site refractive to decontamination using improvised procedures 4 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethical approval was given by Public Health England's Research Ethics Group. As part of a series of human volunteer studies eleven (power = .909, based upon 4 ) participants completed a controlled crossover study in which their skin was dosed separately with MeS (1:1 mixture with vegetable oil) and BeS (each with 4mg/ml of uorescent marker Invisible Red S 4,8 ) at sites on both shoulders (Figure S1). The shoulder was chosen as it was a site refractive to decontamination using improvised procedures 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Table S1 details the participant and study characteristics. 1); improvised dry, improvised wet (RWR, 4 ), interim (a bespoke high-volume showering corridor 8 ), SOR (an MDU with detergent and annel, 8 ) and a no-decontamination control. Interventions were conducted at a time post simulant application equivalent to operational expectations (Figure S2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of human volunteer trials conducted by Collins et al [ 55 ] using improvised dry/wet, interim wet, and mass decontamination showering methods at realistic timescales showed variable removal of two chemical warfare agent simulants, MeS and benzyl salicylate (BeS) from the hair and scalp of volunteers. Noting the limitations associated with the semi-quantitative sampling methods, dry decontamination was shown to reduce the amount of MeS and BeS remaining on the hair although results were only significant for the removal of BeS.…”
Section: Key Findings From Mass Casualty Decontamination Researchmentioning
confidence: 99%
“…Until recently, with the exception of one study in which an oil-based simulant was used [ 79 ] all human volunteer decontamination studies, including those that have informed UK and US guidance used the simulants MeS or ethyl lactate (EL) [ 18 , 34 , 78 , 80 , 81 , 82 , 83 ]; volatile compounds (vapour pressures 4.6 Pa and 500 Pa at 25 °C) with similar physicochemical properties to sulphur mustard and sarin, respectively [ 84 ]. The range of chemical simulants safe to apply to humans is understandably more limited compared to those for in vitro studies [ 84 ] but James et al [ 56 ] recently identified BeS as a simulant for more persistent, lipophilic chemicals such as Novichok [ 57 ] and subsequently demonstrated its suitability for evaluating decontamination efficacy in human trials [ 55 , 59 , 85 ].…”
Section: Future Research Prioritiesmentioning
confidence: 99%